Class, education and social mobility: Madrid, 1880-1905 - Francisco J. Beltrán Tapia; Santiago de Miguel Salanova (European Historical Economics Society (EHES), 2019)
Relying on an extremely rich data set of individuals living in Madrid in 1880 and 1905, this article explores the relationship between class, access to education and social mobility. In order to do so, we first focus on children and assess the probability of being literate according to their parents' socio-economic status. Although inequality in education declined during the period under study, this social gap was still substantial in 1905. Linking where these children lived with the location of public schools, we show that, although the expansion of the supply of schools improved access to education of children from disadvantaged backgrounds, the public effort was clearly insufficient to overcome the challenges these families faced. Lastly, we analyse the returns to education by studying social mobility. In this regard, we have matched the children existing in our sample in 1880 with their corresponding adult-selves in 1905, 25 years later, using record linkage techniques. Our analysis shows that letting literate enhanced children's chances of moving up the social ladder. Taking together, our results show that high inequality levels, together with an inadequate schooling system, prevented a significant fraction of the schooling-age population to access education and thus limited subsequent economic growth.
Keywords: N33; J24; I24; 330; Inequality; schooling; education; social mobility